Predictors of preventive behavior of nosocomial infections in nursing staff: a structural equation model based on the social cognitive theory - Seyed-Mousa Mahdizadeh; Seyedeh Belin Tavakoly Sany; Davood Robat Sarpooshi; Alireza Jafari; Mehrsadat Mahdizadeh (BMC, 2021)
Abstract Background The occurrence of nosocomial infections remains a health threat to patients and hospital staff. This study applied social-cognitive theory for predicting determinants of nosocomial infections control behaviors in hospital nursing Staff. Methods In this cross-sectional study, 280 nurses and assistant nurses were selected by random sampling from intensive care wards including CCU, ICU, NICU, dialysis of educational hospitals in Mashhad, Iran in 2020. Data were collected using a 5-point Likert scale structural questionnaire based on social cognitive theory constructs. Using the structural equation modeling method, direct and indirect relationships of social cognitive factors on preventive behaviors of nosocomial infections were analyzed via AMOS 23.0. Results Our results showed that self-regulation, outcome expectations, and barrier constructs had a direct effect on behavior and the highest effect was related to self-regulation structure (p < 0.001). The constructs of social support, modeling, perceived environment and Task self-efficacy had an indirect effect on behavior and the most impact was related to the constructs of perceived environment (p < 0.05). Conclusion Considering that self-regulation, outcome expectation and barriers have a significant effect on following the preventive behaviors of nosocomial infections in nursing staff. It is suggested that policymakers and planners try to reduce barriers, strengthen behavioral motivation, and empower nursing staff by teaching self-regulatory strategies.